2001
DOI: 10.1177/088626001016005003
|View full text |Cite
|
Sign up to set email alerts
|

Rape Myth Acceptance Among College Women

Abstract: Using data from a survey of 623 undergraduate college women, this study explores the impact of race and prior sexual assault victimization on the acceptance of rape myths. No substantial differences emerged between Black and White women. This finding differs from earlier studies that found more support for rape myths among Blacks. Victims and nonvictims also revealed very similar attitudes, suggesting that socialization patterns or belief in a “just world” may encourage victims to retain their support of some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(48 citation statements)
references
References 15 publications
6
41
1
Order By: Relevance
“…In corroborating a defensive attribution hypothesis, some studies announce that chronic household violence will curb the support of rape myths (Anderson et al, 1997;Carmody & Washington, 2001;Follette, Polusney, & Naugle, 1996). However, paradoxically, other studies argue that people who are bullied or brutalized by family members are more likely to identify with aggressors and rapists (Arriaga & Foshee, 2004;Forbes & AdamsCurtis, 2001;Gwartney-Gibbs, Stockard, & Bohmer, 1987).…”
Section: Familial Peer Contexts and Educational Forces Behind Rape mentioning
confidence: 90%
See 2 more Smart Citations
“…In corroborating a defensive attribution hypothesis, some studies announce that chronic household violence will curb the support of rape myths (Anderson et al, 1997;Carmody & Washington, 2001;Follette, Polusney, & Naugle, 1996). However, paradoxically, other studies argue that people who are bullied or brutalized by family members are more likely to identify with aggressors and rapists (Arriaga & Foshee, 2004;Forbes & AdamsCurtis, 2001;Gwartney-Gibbs, Stockard, & Bohmer, 1987).…”
Section: Familial Peer Contexts and Educational Forces Behind Rape mentioning
confidence: 90%
“…Although numerous studies highlight that self-identified rape victims cast less aspersions on other victims (Anderson et al, 1997;Littleton & Axsom, 2003;Mason, Riger, & Foley, 2004;Peterson & Muehlenhard, 2004 ), another set of studies concludes that being a victim of rape is not connected to the repudiation of rape myths (Burt, 1980;Carmody & Washington, 2001;Mynatt & Allgeier, 1990;Reilly, Lott, Caldwell, & DeLuca, 1992).…”
Section: Victimization and Rape Perceptionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Rape myths are those ideas or beliefs that “deny or minimize victim injury or blame the victims for their own victimization” [32]. Rape myths that are commonly accepted include, the woman deserved to be raped; she asked for it through her provocative behavior or dress; there was not much physical damage so it was not rape; stranger rape is more prevalent than acquaintance rape; and, a woman cannot be raped by her husband [32-35]. There is a growing body of evidence showing that despite years of public education about sexual violence, rape myths and gender stereotypes are still accepted, believed and propagated by communities [32-35].…”
Section: Introductionmentioning
confidence: 99%
“…Yanowitz (2006), for example, surveyed 102 students to see how they conceptualized stalking. Carmody and Washington (2001) conducted a mail survey with 623 students to assess the impact of race and prior sexual assault victimization on the acceptance of "rape myths." Other researchers have used college students as a sample to examine the causes of physical assault in dating relationships (Mahlstedt & Welsh, 2005), the ties between alcohol use and sexual victimization (Kaysen, Neighbors, & Martell, 2006), and the bullying experiences of elementary school, high school and college students (Chapell, Hasselman, Kitchin, Lomon, MacIver & Sarullo, 2006).…”
Section: Behavioral Studies and College Studentsmentioning
confidence: 99%